Perception of Microentrepreneurs in the Public Sector by the National Institute of the Entrepreneur as Public Policy (GEON Journal (Management, Organizations and Business), 2017)
The entrepreneurial phenomenon has become more important in recent years and it is therefore very important that the different orders of government of any nation, assume a responsible position before this fact, especially, when they identify what are the main characteristics and motivations they have The entrepreneurs to start a company, which allows to have an X-ray of what are the requirements for people to decide to undertake and those who have already achieved it can be maintained and able to grow and that is why public policies implemented for this purpose, charge a Greater importance, especially in those countries that are developing, such as Mexico.     This allows us to reflect the relevance of the fact that entrepreneurs who have identified a good investment idea and already established entrepreneurs require regular support of a financial type that allows them to generate conditions of competitiveness and adaptation to new environments Economic and social, that cause that the entrepreneurs have to be more innovative and creative.     For this reason, the present research seeks to analyze how entrepreneurs perceive all micro and small size in the municipality of Puebla in Mexico, one of the public policies implemented by the current Federal Government called INADEM (National Institute of Entrepreneurs) That two of the objectives established by this Institute are: a) To promote a legal and regulatory environment conducive to the development of Entrepreneurs and MSMEs; B) Promote access to finance and capital for entrepreneurs and MSMEs.
Keywords: Entrepreneurs; Business; Public Policy; Goverment and competitiveness